Philosophy of Education and Pedagogy: The Art of Enriching Interactions In Education - Dewirahmadanirwati Dewirahmadanirwati; M Zaim (Jurnal Ilmiah Langue and Parole, 2023)
This article aims to examine the role and purpose of the philosophy of education while identifying the unique dynamics of its association with educational practice and pedagogical science. Within the realm of education, philosophy of education and pedagogy explore distinct facets of the same subject matter. Rather than acting as competitors, these disciplines, with diverse research functions, possess the potential for mutual complementarity and reciprocal enhancement of their cognitive capacities. The outcomes reveal that as a branch of applied philosophy, philosophy of education does not serve as a direct tool for influencing educational practice. Instead, its primary purpose lies in facilitating comprehension and understanding of crucial issues in the theory and practice of education. In this relationship, pedagogy acts as a mediator, playing a crucial role. In conclusion, the most productive form of the relationship between the philosophy of education and pedagogical science is one of interaction. This interaction fosters mutual enrichment, strengthens their research capabilities, and allows for the fullest realization of their distinct functions. Pedagogy, in particular, has the flexibility to choose from philosophical and educational concepts to develop theories, which are validated through experimentation and directly applied in practice. Philosophy of education, meanwhile, realizes its theoretical functions across all stages of educational activity.